Recent Progress on Preparation Strategies of Liquid Crystal Smart Windows - Luo, Linfeng; Liang, Yinghui; Feng, Yuting; Mo, Dan; Zhang, Yang; Chen, Jiawen (Crystals (Basel), 2022)
Liquid crystal (LC) smart windows that are able to regulate natural light by changing the optical transmittance in response to external stimulus have become an effective way to reduce building energy consumption. The rapid development of technology has brought out a variety of responsive smart windows suitable for daily life, including electrical-, thermal-, and photo-responsive ones. In this review, the recent progress in LC smart windows that switch between transparent and opaque states by different stimuli is overviewed. The preparation strategies for single-/dual-responsive smart windows are outlined, exclusively concentrating on the functional design and working principle. Furthermore, the advantages and current drawbacks of smart windows for each response mode are briefly described. Finally, a perspective on the direction of future responsive LC smart windows is discussed.